Problematic aspects of the prosecutor’s participation in court proceedings under the agreements - Гловюк, І.В; Андрусенко, С.В (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2015)
The article focuses on prosecutor’s role in proceedings on agreements basis. The procedural and tactical features of prosecutor’s role in the proceedings, depending on the type of transaction are defined. The conclusion about the necessity to develop the forensic recommendations system for maintaining of state prosecutor in proceedings on agreements basis is made. Tactics of the prosecutor in the proceedings on the basis of agreements due, firstly, the type of transaction; secondly, the moment of its conclusion; thirdly, the position of the accused and the victim in court. The task of the prosecutor is to express well-founded legal opinion on the issue of compliance with the requirements of the agreement Criminal and Criminal Procedural Code of Ukraine and voluntary deal, and active participation in the trial study of these issues will help enactment legitimate and reasonable judgment or decree.

Статтю присвячено дослідженню проблеми участі прокурора у судовому провадженні на підставі угод. Визначено процесуальні та тактичні особливості участі прокурора у судовому провадженні залежно від виду угоди. Зроблено висновок про необхідність розробки системи криміналістичних рекомендацій щодо тактики підтримання прокурором державного обвинувачення у судовому провадженні щодо угод
ПРОБЛЕМНІ АСПЕКТИ УЧАСТІ ПРОКУРОРА У СУДОВОМУ ПРОВАДЖЕННІ НА ПІДСТАВІ УГОД
Keywords: prosecutor; state prosecution; plea bargaining; agreement on reconciliation; proceeding; прокурор; державне обвинувачення; угода про визнання винуватості; угода про примирення; судове провадження